2013
DOI: 10.1016/j.joca.2013.08.006
|View full text |Cite
|
Sign up to set email alerts
|

Sustained clinical and structural benefit after joint distraction in the treatment of severe knee osteoarthritis

Abstract: Clinical improvement by KJD treatment is sustained for at least 2 years. Cartilage repair is still present after 2 years (MRI) and the newly formed tissue continues to be mechanically resilient as shown by an increased JSW under weight-bearing conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
135
2
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(150 citation statements)
references
References 36 publications
7
135
2
2
Order By: Relevance
“…The ARomDe score monitors the quality of life via the measurement of three dimensions, including pain and function recovery and behavior. It is consistent with many previous studies, which generally evaluate the improvement of models and human with knee osteoarthritis via the achievement of pain relief [2,7,14,19,20,26,28,29] and function recovery [1,2,26,27] and emotional behavior [1,19,20,27].…”
Section: Special Issue On "Human Stem Cells and Transplantation": Open supporting
confidence: 90%
See 1 more Smart Citation
“…The ARomDe score monitors the quality of life via the measurement of three dimensions, including pain and function recovery and behavior. It is consistent with many previous studies, which generally evaluate the improvement of models and human with knee osteoarthritis via the achievement of pain relief [2,7,14,19,20,26,28,29] and function recovery [1,2,26,27] and emotional behavior [1,19,20,27].…”
Section: Special Issue On "Human Stem Cells and Transplantation": Open supporting
confidence: 90%
“…In severe knee OA, conservative treatment only provides temporary relief of clinical symptoms. Total knee replacement is required [7]. However, no treatment has been shown as ideal, so far, regarding their side effects.…”
Section: Introductionmentioning
confidence: 99%
“…In all these studies, they have demonstrated that the joint space width (JSW) on weight-bearing X-rays had increased after treatment. In a few studies they have also performed arthroscopic evaluation 8,9,12 and/or MRI evaluation 9,10,12 to showed cartilage repair after the joint distraction therapy. Intema et al 10 analyzed biochemical markers for collagen type II turnover and showed an increase of synthesis over release, suggesting that the hyaline nature of the newly formed tissue.…”
Section: Introductionmentioning
confidence: 99%
“…Only one prospective open uncontrolled trial has been performed. Follow-up of the 20 treated patients is reported on at one, two, and five years post-treatment [43,44] (ms under review). Clinical benefit with cartilaginous tissue repair has been demonstrated to sustain for up to five years after treatment in over three-quarter of the patients treated.…”
Section: Introductionmentioning
confidence: 99%